DETERMINAN KEMISKINAN DI JAWA DAN SUMATERA, INDONESIA - Roosemarina Anggraini Rambe (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
The research objective is to analyze the role of government expenditure, the interaction between the previous government expenditure and poverty rate, economic growth, and local government location on poverty alleviation in Java and Sumatra, Indonesia. The analytical method used is multiple linear regression. The result shows that government expenditure and economic growth have a significant negative impact on the poverty rate. Conversely, the interaction of government expenditure and poverty rate in the previous year has a significant positive impact on the poverty rate of the current year. For the location variable, the poverty rate in Java is significantly lower than Sumatra. Therefore, it is recommended for the government to shift its focus to poverty, aside from their typical feeding program. Besides, the government is also advised to make appropriate regulations so that economic growth can be utilized better to alleviate the poverty rate.